SIASAT-SIASAT NATURALISME DALAM FILSAFAT HUKUM: SEBUAH KONTRIBUSI FILSAFAT ILMU - Sebastian, Tanius (Faculty of Law, Parahyangan Chatolic University, 2015)
Naturalism is one of the main topics that explore the philosophical discourse. This article intends to discuss the philosophical problems of naturalism in jurisprudence. The argumentations of naturalism have affected the configuration of methodological debate in jurisprudence; between the descriptive approach and the evaluative approach. By reviewing the project of naturalism in metaphysics and epistemology and then scrutinizing how the ideas of naturalism work in jurisprudence, this article will exhibit a contribution of the philosophy of science to the scientific reflection of law. The development of naturalism creates challenges and chances at once for methodological tracing in the philosophy of law.